Beyond Numbers: Determining the Socioeconomic and Livelihood Impacts of African Swine Fever and Its Control in the Philippines - Cooper, Tarni L.; Smith, Dominic; Gonzales, Mark Jaypee C.; Maghanay, Marlon T.; Sanderson, Sunny; Cornejo, Marie Rachelle Jane C.; Pineda, Lohreihleih L.; Sagun, Rose Ann A.; Salvacion, Oliver P. (Frontiers in Veterinary Science, 2022)
The impacts of African Swine Fever (ASF) have most frequently been described quantitatively though it is increasingly acknowledged these impacts extend well beyond numbers. During 2020, a multidisciplinary team of researchers developed a framework for Socioeconomic and Livelihood Impact Assessment (SELIA) of livestock diseases in smallholder communities. Two key innovations within this SELIA framework are the integration of sustainable livelihoods concepts to capture rich information beyond financial impacts, and the inclusion of stakeholders across the value chain, beyond farmers. This paper focuses on the findings from one of the first applications of the SELIA framework. In late 2020 the research team applied participatory tools from the SELIA Framework (8 focus group discussions, 14 key informant interviews, and 2 network mapping activities) to gather data to describe the impact of ASF in backyard pig-farming communities and value chains. This was undertaken across two locations in the Philippines, in turn highlighting potential leverage points for intervention. Owing to COVID-19 travel restrictions and risks, modifications to training and field activities were made. Findings from focus groups and interviews revealed the deep, emotional impacts of ASF and the associated control measures. Pigs were considered pets by many farmers and some women described them as being like their children. Animal health-workers (AHWs) also recognised the emotional toll on farmers and were sometimes strongly criticised by community members due to their involvement in depopulation campaigns. Misinformation early in the epidemic also led farmers to hide their animals from AHWs, and to dispose of them inappropriately. While the overall impact of ASF on society was negative, the impacts across different communities, scales of production and different value chain actors varied. The losses experienced by backyard farmers resulted in significant losses to linked value chain actors, such as input suppliers. This trial application of the SELIA framework revealed some complex and varied impacts of ASF. This included significant differences in livelihood and socio-economic impacts amongst different actors within value chains and also among different categories of actors (for example small, medium and large-scale traders). Repeated themes and triangulated findings suggest two leverage points for further consideration. Firstly, it is recommended a One Welfare approach to ASF control in the Philippines is explored. Emphasising careful communication between animal health-workers and farmers, and humane and sensitive pig depopulation practices. Secondly, consideration of ASF support programs tailored to sectoral and specific communities is recommended.